FAMILY CONFLICT REFLECTED IN KEVIN KWAN’S “RICH PEOPLE PROBLEM”; A SOCIOLOGICAL APPROACH - Indah Purnama; Ayu Melati Ningsih (PHILOLOGY Journal of English Language and Literature, 2021)
The objective of the research was to analyze the family conflict that was reflected in the novel Rich People Promblem. This research used a sociological approach and social action theory. This research used a qualitative research. This research was taken from the novel "Rich People Problem" written by Kevin Kwan's. This research rose the following problems: 1). The type of family conflict reflected in Kevin Kwan's novel "rich people problem.? 2). What was the cause of family conflict in the novel Rich people problem.?. So that it can be known the causes and types of family conflicts contained in the novel Rich people problem.The result of the research was that there were two kind family conflicts,first types of family conflict was the internal and external, second cause of family conflict was the language difference and tradition and heritage.